"Does Physical Exercise Promote Health Benefits for Diabetic Patients during the COVID-19 Pandemic?": A Systematic Review - Erivaldo de Souza; Daniela Meneses-Santos; Josué Cruz Santos; Felipe J. Aidar; Carla Roberta de Oliveira Carvalho; Jymmys Lopes dos Santos; Anderson Carlos Marçal (MDPI AG, 2023)
Patients affected by COVID-19 are prone to facing disorders in multiple systems and organs, which can lead to deleterious diseases; in addition, people with pre-existing diseases may be more prone to the worst outcomes, and the most vulnerable are patients with type 1 and type 2 diabetes mellitus. The aim of this systematic review was to evaluate the effects of physical activity and/or physical exercise prescribed to individuals with diabetes on the maintenance of plasma glucose and glycated hemoglobin during the COVID-19 pandemic. Studies were found by searching PubMed, SCOPUS, Embase, Web of Science, SciELO, LILACS, SportDiscus, Bireme/BVS and Google Scholar databases. The inclusion criteria were articles that addressed only patients with type 1 or type 2 diabetes (T1D and T2D) who had evaluated the level of physical activity or physical exercise and described the effects on plasma glucose and/or glycated hemoglobin in cross-sectional, retrospective, and observational studies, meeting the main criteria established by GRADE. The PICO and GRADE strategies were used to select and assess the methodological quality of studies. Two reviewers searched and selected the articles in databases independently and blindly, during which oppositions and disagreements about the inclusion of articles were discussed and resolved by a third reviewer. Evidence corroborates that levels of physical activity were reduced due to the lockdown, leading to increased body weight and worse glycemic control. On the other hand, individuals with diabetes mellitus (DM) (T1D and T2D) who maintained and/or increased levels of physical activity or physical exercise showed reduced plasma glucose and glycated hemoglobin (HbA1c) levels. Adequate levels of physical exercise and physical activity are beneficial for glucose and HbA1c control in diabetic patients (type 1 or type 2). In addition, maintaining adequate levels of physical activity can contribute to reducing health problems when these patients are infected with COVID-19.